CDK4/6 inhibition in advanced chordoma: final results of the NCT PMO-1601 trial - Teleanu, Maria-Veronica; Heilig, Christoph E.; Pirmann, S.; Hamacher, R.; Bauer, S.; Gaidzik, V. I.; Mayer-Steinacker, R.; Al-Sabah, J.; Roldan Pinzon, S. S. L.; Süße, Heike; Freitag, A.; Horak, Peter; et al. (ESMO open, 2025)
Background - This study aims to evaluate antitumor response of palbociclib in patients with advanced chordoma, an ultra-rare cancer without approved systemic therapy. Previous data showed that palbociclib reduced cell viability and proliferation in CDKN2A-deficient chordoma cell lines. - Patients and methods - We conducted a phase II single-arm, open-labeled trial on palbociclib in adult patients with advanced chordomas with p16 (by immunohistochemistry) or CDKN2A (by genomic analysis) loss along with retained CDK4/6 and RB1 expression (by immunohistochemistry or RNA sequencing). Based on CDK4/6/pRB (S780) immunohistochemical expression patterns, a responder versus non-responder signature was assigned. The study used a Simon optimal two-stage design with the primary endpoint of disease control rate (DCR) by RECISTv1.1 after six cycles. Secondary endpoints included progression-free survival, overall survival, and biomarker analysis. The study was considered positive if 25% of patients reached the primary endpoint. - Results - Twenty-eight patients with a median age of 59 years were assessed for the primary endpoint. After a median follow-up of 28 months, the DCR was 39%, with 11 patients achieving stable diseases. No objective responses were obtained. The median progression-free survival was 5.6 months, and the median overall survival was 24.6 months. Treatment was well tolerated without new safety signals. There was no correlation between immunohistochemical responder phenotypes and outcome. Biomarker analysis identified additional clinically actionable alterations affecting PIK3CA, PTEN, MTAP, or MET genes, and druggable pathways by transcriptomic analysis. - Conclusion - Although antitumor activity was modest, the trial met its primary endpoint. Molecularly tailored combination therapies should be considered in the future to improve efficacy.
Gesehen am 24.11.2025